Pelatihan Berbahasa Indonesia Yang Santun Dalam Chat Whatsapp Melalui Pendekatan Linguistik Bagi Remaja - Sugiarti; M. Muklas; M. Albar (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to improve adolescents’ ability to use polite Indonesian in communication through the WhatsApp application by applying a linguistic approach. The background of this activity is the increasing use of informal language, excessive abbreviations, and impolite expressions in adolescents’ digital conversations. The implementation method involves participatory training, including the delivery of linguistic materials, interactive discussions, and hands-on practice in analyzing and revising WhatsApp conversation samples. The training materials focus on understanding language politeness, appropriate word choice, sentence structure, and contextual language use in digital communication. The results indicate an improvement in adolescents’ awareness and understanding of the importance of using polite and context-appropriate Indonesian. Participants were able to distinguish between formal and informal language varieties and apply them appropriately in WhatsApp communication. This activity contributes positively to the development of polite language attitudes while strengthening the role of applied linguistics in fostering Indonesian language use among adolescents.